2013
DOI: 10.1093/gerona/glt050
|View full text |Cite|
|
Sign up to set email alerts
|

Insomnia and Health Services Utilization in Middle-Aged and Older Adults: Results From the Health and Retirement Study

Abstract: In this study, insomnia symptoms experienced by middle-aged and older adults were associated with greater future use of costly health services. Our findings raise the question of whether treating or preventing insomnia in older adults may reduce use of and spending on health services among this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 21 publications
1
52
3
Order By: Relevance
“…However, while such measurement error might reduce the strength of association, we believe it is not the primary reason why we found no association between social participation and the insomnia symptom scale. First, these questions have been used in prior studies that yielded valuable insights about insomnia in the general population (e.g., Kaufmann et al, 2013). Second, while the reliability of the scale is not high, it is within the acceptable range for an additive scale.…”
Section: Discussionmentioning
confidence: 99%
“…However, while such measurement error might reduce the strength of association, we believe it is not the primary reason why we found no association between social participation and the insomnia symptom scale. First, these questions have been used in prior studies that yielded valuable insights about insomnia in the general population (e.g., Kaufmann et al, 2013). Second, while the reliability of the scale is not high, it is within the acceptable range for an additive scale.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with past research (Kaufmann et al, 2013), the responses of “almost always”, “often”, or “sometimes” to the four questions were coded as indicators of poor sleep quality. These four items were summed as an index that ranged from 0 to 4, with higher scores representing worse sleep quality.…”
Section: Methodsmentioning
confidence: 99%
“…According to the Kaiser Family Foundation, inpatient care in 2011 accounted for the greatest portion of spending for Medicare beneficiaries aged 65 and older. 4 Prior studies [5][6][7] suggested that sleep disturbances and sleep disorders including insomnia are associated with greater healthcare utilization. These studies have not focused specifically on older adult populations, where the burden of sleep disorders and risk of inpatient hospitalizations are highest, and have also relied on self-reported sleep data that may not be as accurate as more objective sleep measures from actigraphy or polysomnography.…”
Section: Introductionmentioning
confidence: 99%